2019
DOI: 10.1021/acs.jmedchem.9b00561
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Inhibitors of Protein–Protein Interactions Targeting Lysine, Tyrosine, or Histidine Residues

Abstract: We have recently reported a series of Lys-covalent agents targeting the BIR3 domain of the X-linked inhibitor of apoptosis protein (XIAP) using a benzamide-sulfonyl fluoride warhead. Using XIAP as a model system, we further investigated a variety of additional warheads that can be easily incorporated into binding peptides and analyzed their ability to form covalent adducts with lysine and other amino acids, including tyrosine, histidine, serine, and threonine, using biochemical and biophysical assays. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
143
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(148 citation statements)
references
References 62 publications
(113 reference statements)
5
143
0
Order By: Relevance
“…Indeed, recent reports are proposing a Lysinome or a Tyrosinome as an ensemble of targets that present targetable Lys or Tyr residues in proximity of their binding sites in enzymes [12] . Our recent application included a side by side investigation of the merits and pitfalls of aryl‐sulfonyl fluorides and aryl‐fluorosulfates as possible electrophiles to target Lys, Tyr, and His in protein–protein interactions [1b] . We found that when properly juxtaposed to a binding site Lys residue, aryl‐fluorosulfates approach the proper balance of stability, reactivity and cell permeability, similar to what is observed with Cys and acrylamides.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Indeed, recent reports are proposing a Lysinome or a Tyrosinome as an ensemble of targets that present targetable Lys or Tyr residues in proximity of their binding sites in enzymes [12] . Our recent application included a side by side investigation of the merits and pitfalls of aryl‐sulfonyl fluorides and aryl‐fluorosulfates as possible electrophiles to target Lys, Tyr, and His in protein–protein interactions [1b] . We found that when properly juxtaposed to a binding site Lys residue, aryl‐fluorosulfates approach the proper balance of stability, reactivity and cell permeability, similar to what is observed with Cys and acrylamides.…”
Section: Discussionmentioning
confidence: 71%
“…Typical of non‐covalent targeting agents, compound 1 displayed a ΔTm ∼5 °C (regardless of the pre‐incubation time of either 30 min or 2 h, Table 1), while putative covalent compounds showed significantly larger shifts (ΔTm of >20 °C; Table 1). [1b] However, some agents displayed a larger denaturation thermal shift only at the longer incubation time (namely agents 9 and 11 ), suggesting a slower reaction with the target. Compound 4 , compatible with its lack of stability in buffer (Table 1), did not induce large ΔTm values nor displayed low nanomolar affinity in the DELFIA assay (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tetrapeptide mediates its interactions with various members of the IAP family, including the Xlinked inhibitor of apoptosis protein (XIAP). In addition, Lys-covalent inhibitors have been designed with a benzamide-sulfonyl fluoride warhead to target the BIR3 domain of XIAP [60,61].…”
Section: Structure-guided Design Of Covalent Inhibitorsmentioning
confidence: 99%
“…In another study, the structure-based biophysical and biochemical approaches were used to develop different kinds of warheads which can easily form covalent adducts with alternative amino acids such as histidine, threonine, serine, and tyrosine [62]. It was found that aryl-fluoro sulfate electrophiles can form covalent bonds with Lys, Tyr, and His residues in PPIs [61]. With the tremendous progress and resurgence for covalent drugs, these successful cases present valuable and novel ideas for covalent PPI inhibitors and suggest the possibility for extending the target cysteinome range to other residues.…”
Section: Structure-guided Design Of Covalent Inhibitorsmentioning
confidence: 99%